MASQUELET PROCEDURE: A NOVEL APPROACH FOR ADDRESSING POST-TRAUMATIC BONE DEFECTS - ILIAS BASHA AM; SHAIK RASOOL; K ANUSHA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: This study aims to assess the efficacy of the Masquelet technique in addressing post-traumatic long bone defects. Through a two-stage process involving temporary spacer implantation and subsequent staged bone grafting, the objective is to evaluate the technique’s ability to provide mechanical stability, combat infections, and promote successful osseous consolidation, affirming its viability as a surgical solution. Methods: From January 2019 to December 2022, we enrolled patients with post-traumatic bone defects treated using the Masquelet technique. Comprehensive evaluations included injury nature, defect location, soft-tissue condition, defect extent, antibiotics, and cementation duration. We documented fixation methods, infections, and the patient’s current health status for a thorough assessment. Results: In this study of 15 consecutive patients (ten men, five women; average age 43), bone defects were diverse in location (six tibia, four femur, three humerus, one olecranon, and one calcaneum). Eight cases involved closed fractures with infection/nonunion; seven were open fractures (Gustilo II/IIIA). Spacer antibiotic use (gentamicin/vancomycin), bone consolidation, and limb stabilization were successful, with no reported complications in the 40-day average follow-up period. Conclusion: The delayed bone grafting approach, following cement spacer placement, presents a promising solution for significant bone loss in extremity reconstruction. This method, whether immediate or delayed, demonstrates favorable outcomes, with the induced membrane fostering a conducive environment for bone formation. As broader adoption occurs, ongoing clinical evidence will further clarify optimal graft materials, solidifying the efficacy of this innovative strategy in addressing segmental bone loss.